Psychological processes of reading in elementary students of The Callao according to socioeconomic status and gender - Velarde C., Esther (2013)
The objective of this research was to know if there were differences in the psychological processes of reading regarding the socio-economic level and gender of 965 students from 1st to 6 th grade of primary from private and public schools of Callao. For this purpose we adapted and created scales for the battery for Reading processes evaluation - revised (PROLEC-R) by. Cuetos, et al (2007). A comparative descriptive design was used. Significant differences according the socioeconomic level in all grades were found in reading comprehension and oral comprehension. It was also found differences in identification of letters and understanding of sentences (except in 6 th) and punctuation (except in second grade). There are no differ rences in the task of identifying “same–different” words and reading of words (except for 1st grade) and pseudowords (except in 1st and 3 rd) reading and grammatical structures (except 1st and 2nd). Regarding the gender, only difference found was in listening comprehension in favouring the boys. Normative scores were produced lower performance found in all the psychological processes of the reading in the socio-economic E level.